Pesticide residue profiles, dietary risk assessment, and mitigation strategies in citrus production systems of Pakistan - Muneer Abbas; Akbar Hayat; Sohaib Afzaal; Muhammad Ghayoor Husnain; Hira Tariq; Fiaz Hussain; Niaz Hussain; Muhammad Saleem; Dilbar Hussain; Aleena Alam; Wang Dongze; Sohail Abbas (Food Control, 2026)

Enhancement of enzyme-induced carbonate precipitation (EICP) for sustainable soil stabilization in loess slopes using soybean-derived urease and organic nucleating agents - Dequan Kong; Muhammad Muneer; Rong Wan; Xinyang Liu; Masood ur Rahman; Shihao Gu; Mouhong Wang (Engineering Geology, 2026)

Novel synthesis of a sulfur-magnesium compound fertilizer from magnesium-based flue gas desulfurization byproducts - Weiqiang Zhang; Fien Degryse; Zenglian Qi; Min Wang; Muhammad Atif Muneer; Michael J. Mclaughlin; Liangquan Wu; Zhenya Lu; Fusuo Zhang (Journal of Cleaner Production, 2026)

An integrative machine learning and structure-driven drug repositioning strategy for human IRAK4-targeted cancer therapy - Muhammad Waleed Iqbal; Muhammad Ali Raza; Muneer Ahmad; Xinxiao Sun; Jianlong Lv; Xiaolin Shen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Efficacy of aripiprazole and valbenazine in the treatment of tourette syndrome: a systematic review and meta-analysis of randomized controlled trials - Muneeb Ahmad Muneer; Ume Habiba; Shajjia Shehzad; Washija Batool; Dawood Shah; Zain Shahzad; Muhammad Khizar Kirmani; Zohaib Hassan Siddiqui; Areeb Amjad; Ameer Hamza; Muhammad Faizan Khan; Fahad Siddique Butt; et al. (Acta Neurologica Belgica, 2026)

Synergistic Degradation and Cytotoxicity Mitigation of Meloxicam Using UV/Perovskite/H₂O₂ and Gamma/H₂O₂: A Comparative Study - Muhammad Asad Khan; Mohamed A. Habib; Muhammad Imran Kanjal; Majid Muneer; Muhammad Asghar Jamal; Tanveer Hussain Bokhari; Usman Irshad; Ahmed B. M. Ibrahim (Water, Air, & Soil Pollution, 2026)

A Comprehensive Study on Radiation-Assisted Detoxification of Hazardous Industrial Effluents: A Statistical Approach - Saif Ullah; Mohamed A. Habib; Majid Muneer; Muhammad Imran Kanjal; Gulraiz Ahmad; Ahmed B. M. Ibrahim; Rana Muhammad Zulqarnain; Lotfi Mouni (Water, Air, & Soil Pollution, 2026)

Graph-based and molecular modeling approaches to identify TpiA as a noval therapeutic target in Neisseria meningitidis - Sana Abdul Ghaffar; Iqra Muneer; Irfan Manzoor; Roba M. S. Attar; Nada A. Alzunaidy; Basmah F. Alharbi; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem; Muhammad Tahir ul Qamar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Harnessing Paramecium primaurelia for polyhydroxyalkanoate production: optimization of carbon sources for sustainable bioplastic synthesis - Ayesha Arshad; Itrat Zahra; Awais Ibrahim; Usama Shabbir; Shahid Nawaz; Ayesha Liaqat; Roohi Ijaz; Tuba Arooj; Sammi Rasheed; Ayesha Ghauri; Bushra Muneer; Amor Hedfi; et al. (Biologia, 2026)

Bacillus Inoculation Along with Biogas Slurry Mitigates Nickel Stress in Raphanus Sativus by Regulating Ni Accumulation and the Antioxidant Defense System - Iftikhar Ahmad; Shehzad Mehmood; Muhammad Atif Muneer; Aftab Jamal; Amjad Farooq; Muhammad Farhan Saeed; Qasim Ali; Umar Daraz; Nabil Touzout; Adil Mihoub; Jun Zhou (Water, Air, & Soil Pollution, 2025)

Development and characterization of phosphate tailings-based humic acid slow-release fertilizer using ball milling sludge acid activation - Yinxin Xie; Qi Zhang; Deyi Yuan; Yingjie Hu; Caiyuan Guo; Muhammad Atif Muneer; Yafu Tang; Yanhui Xu; Fu Wan; Youzhi Yang (Process Safety and Environmental Protection, 2025)

UV radiation-induced degradation of moxifloxacin: toxicity evaluation and conditions optimization - Muhammad Imran Kanjal; Majid Muneer; Saif Ullah; Saira Sabir; Reguia Boudraa; Abdeltif Amrane; Lotfi Mouni (Euro-Mediterranean Journal for Environmental Integration, 2025)

Evaluating Vertical Distribution of Soil Salinity Patterns Across Multiple Soil Depths in a Semi-Arid Dry Region - Qambar Baloch; Kashif Ali Kubar; Punhoon Khan Korai; Shahmir Ali Kalhoro; Muhammad Bilawal Junaid; Muneer Ahmed Baloch; Zia-ul-hassan; Jawaher Alkahtani; Muhammad Abrar (Journal of Soil Science and Plant Nutrition, 2025)

Response of Fruit Productivity, Soil Physicochemical Properties, and Microbiota to Nitrogen Reduction and Grass Cover Crops in Pomelo Orchard - Shuang Zou; Zongjun Ji; Xinhao Rao; Yingmin Guo; Muhammad Atif Muneer; Siwen Zhang; Delian Ye; Liangquan Wu; Wenhao Yang (Journal of Soil Science and Plant Nutrition, 2025)

Effective synergism of Moringa oleifera with antibiotics, body growth, and decoction replacement - Qandeel Ashraf; Amjad Islam Aqib; Hamid Majeed; Shahbaz Ul Haq; Muhammad Farrukh Nisar; Muhammad Usman; Afshan Muneer; Saba Batool; Farid S. Ataya (South African Journal of Botany, 2024)

Harmonizing traditional and biotechnological approaches to engineer crop microbiomes: Enhancing resilience optimization - Muhammad Siddique Afridi; Abdul salam; Sher Ali; Sumaira; Willian César Terra; Baber Ali; Muhammad Atif Muneer; Gustavo Santoyo (Biocatalysis and Agricultural Biotechnology, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Nitrogen and carbohydrate metabolisms are key factors in maize (Zea mays L.) germination under chromium-induced ROS - Muhammad Imran Atta; Syeda Sadaf Zehra; Zhihang Zhuo; Habib Ali; Malik Waseem Abbas; Syed Naveed Abbas; Sadia Sarwar; Fatima Muneer; Irfan Ahmad; Danpping Xu; Hasham S. Almoallim; Mohammad Javed Ansari (Journal of Plant Diseases and Protection, 2024)

Assessment of residues from common pesticides and associated risks in Pakistan - Muneer Abbas; Sohail Abbas; Niaz Hussain; Muhammad Tariq Javeed; Abdul Ghaffar; Muhammad Nadeem; Mudassar Khaliq; Sana Ullah; Zubeda Parveen; Khalid Ali Khan; Hamed A. Ghramh (Environmental Monitoring and Assessment, 2024)

Green hybrid coagulants for water treatment: An innovative approach using alum and bentonite clay combined with eco-friendly plant materials for batch and column adsorption - Sidra Saqib; Amna Muneer; Ruba Munir; Murtaza Sayed; Muhammad Waqas; Tayyiba Aliyam; Fazila Younas; Mohammad Abul Farah; Mohamed Farouk Elsadek; Saima Noreen (Environmental Research, 2024)

Wet ball milling activated oyster shells for multifunctional slow-release compound fertilizer production - Weiqiang Zhang; Dian jin; Caixia Liu; Muhammad Atif Muneer; Huanhuan Zhu; Taoyu Ren; Hongnan Xu; Jingwen Wang; Zhenya Lu; Deyi Yuan; Yafu Tang (Chemical Engineering Journal, 2024)

Establishing quality evaluation standards for pomelo fruit: The role of harvesting time and appearance characteristic - Xiaojun Yan; Muhammad Atif Muneer; Mengting Qin; Jie Ou; Xiaohui Chen; Zhiyuan He; Yedong Liu; Zhihan Cheng; Da Su; Rongrong Liu; Liangquan Wu (Postharvest Biology and Technology, 2024)

Synthesis of polymeric ferrite composites (Ni-CoFe2O4/Chitosan, Zn-NiFe2O4/Starch, Co-NiZnFe2O4/Polyaniline, Ni doped CrZnFe2O4/Alginate, and Cr doped ZnCoFe2O4/PVA) for the removal of reactive golden yellow-160 dye from wastewater - Ghulam Mustafa; Ruba Munir; Bushra Sadia; Fazila Younas; Murtaza Sayed; Amna Muneer; Muhammad Fahad Sardar; Gadah Albasher; Saima Noreen (Journal of Environmental Chemical Engineering, 2024)

Exposure to heavy metals, antioxidant status, and the interaction of single nucleotide polymorphisms in the genes CAT rs7943316, GSTP1 rs1695, as well as GSTM1 and GSTT1 genes, among workers in occupational settings - Sosan Andleeb Khan; Syed Muhammad Nurulain; Rashid Nazir Qureshi; Amina Zafar; Zarish Riaz; Aneela Shoukat; Zahid Muneer; Nazia Bibi; Saqlain Raza; Sabir Hussain; Syed Tahir Abbas Shah (Environmental Toxicology and Pharmacology, 2024)

Construction and Utilization of Innovative Zeolite/Perovskite/Graphene Oxide, Zeolite/Chitosan/Graphene Oxide, and Zeolite/Biochar/Graphene Oxide Nanohybrid Composites for Adsorptive Remediation of Cationic Dye from Wastewater - Nageen Mushtaq; Ruba Munir; Muhammad Zia-ur-Rehman; Zia ul-Haq; Muhammad Zeeshan Bashir; Amna Muneer; Hina Ambreen; Saima Noreen (Water Conservation Science and Engineering, 2024)

Exploring zeolite-based composites in adsorption and photocatalysis for toxic wastewater treatment: Preparation, mechanisms, and future perspectives - Iqra Liaquat; Ruba Munir; Naseer Ahmed Abbasi; Bushra Sadia; Amna Muneer; Fazila Younas; Muhammad Fahad Sardar; Muhammad Zahid; Saima Noreen (Environmental Pollution, 2024)

Biochar imparted constructed wetlands (CWs) for enhanced biodegradation of organic and inorganic pollutants along with its limitation - Ruba Munir; Amna Muneer; Bushra Sadia; Fazila Younas; Muhammad Zahid; Muhammad Yaseen; Saima Noreen (Environmental Monitoring and Assessment, 2024)

Assessing the climate vulnerability of mountain agriculture: a case study of Haramosh Valley in Central Karakoram, Pakistan - Muneer Alam; Muhammad Zafar Khan; Farida Begum; Tasawar R. Baig (Environment, Development and Sustainability, 2024)

Mitigating life-cycle environmental impacts and increasing net ecosystem economic benefits via optimized fertilization combined with lime in pomelo production in Southeast China - Xiaojun Yan; Yifei Ma; Kunpeng Kong; Muhammad Atif Muneer; Lijun Zhang; Yadong Zhang; Zhihan Cheng; Ziwei Luo; Changcheng Ma; Chaoyuan Zheng; Wenhao Yang; Jiuxin Guo; et al. (Science of The Total Environment, 2024)

Melatonin supplementation alleviates drought stress in peach (Prunus persica) seedlings by improving photosynthesis, root morphological traits, and antioxidant defense system - Shahid Iqbal; Faisal Hayat; Mujahid Hussain; Naveed Mushtaq; Muneer Rehman; Alaiha Asif; Ummara Khan; Muhammad Adnan Shahid (Acta Physiologiae Plantarum, 2024)

Enhanced electrochemical conversion of CO2 into formic acid using PbSO4/AtSn electrode: Catalyst synthesis and process optimization - Muhammad Arsalan; Dina Ewis; Nafis Mahmud; Muneer M. Ba-Abbad; Mazen Khaled; Muftah H. El-Naas (Journal of Environmental Chemical Engineering, 2023)

Synergistic effect of β-sitosterol and biochar application for improving plant growth of Thymus vulgaris under heat stress - Khadiga Alharbi; Amir Abdullah Khan; Haifa Abdulaziz Sakit Alhaithloul; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Saeedah Sallum Aloufi; Awatif M. Abdulmajeed; Muhammad Atif Muneer; Suliman M.S. Alghanem; Muhammad Zia-ur-Rehman; Muhammad Usman; Mona H. Soliman (Chemosphere, 2023)

Effects of soil amendments on soil acidity and crop yields in acidic soils: A world-wide meta-analysis - Siwen Zhang; Qichao Zhu; Wim de Vries; Gerard H. Ros; Xiaohui Chen; Muhammad Atif Muneer; Fusuo Zhang; Liangquang Wu (Journal of Environmental Management, 2023)

Inconsistent responses of soil bacterial and fungal community's diversity and network to magnesium fertilization in tea (Camellia sinensis) plantation soils - Wenhao Yang; Zongjun Ji; Aolin Wu; Dongdong He; Christopher Rensing; Yanhua Chen; Chengcong Chen; Huihuang Wu; Muhammad Atif Muneer; Liangquan Wu (Applied Soil Ecology, 2023)

Emerging trends in insect sex pheromones and traps for sustainable management of key agricultural pests in Asia: beyond insecticides—a comprehensive review - Aleena Alam; Sohail Abbas; Arzlan Abbas; Muneer Abbas; Faisal Hafeez; Muhammad Shakeel; Feng Xiao; Chen Ri Zhao (International Journal of Tropical Insect Science, 2023)

Chronic exposure to electronic waste poses risk to liver toxicity with molecular interaction of GSTM1, GSTT1 null variants, and GSTP1 - Aneela Shoukat; Syed Muhammad Nurulain; Sabir Hussain; Sosan Andleeb Khan; Hussain Ahmed; Zahid Muneer; Syed Tahir Abbas Shah; Saqlain Raza; Syed Ali Musstjab Shah Eqani (Environmental Pollution, 2023)

Farm households' perception and adaptation to climate change in relation of food crop productivity in Pakistan - Seher Muneer; Khuda Bakhsh; Rafaqet Ali; Muhammad Asim Yasin; Muhammad Asif Kamran (Environment, Development and Sustainability, 2023)

Green metal oxides coated biochar nanocomposites preparation and its utilization in vertical flow constructed wetlands for reactive dye removal: Performance and kinetics studies - Ruba Munir; Khuram Ali; Syed Abbas Zilqurnain Naqvi; Amna Muneer; Muhammad Zeeshan Bashir; Muhammad Aamer Maqsood; Saima Noreen (Journal of Contaminant Hydrology, 2023)

Plant community and soil available nutrients drive arbuscular mycorrhizal fungal community shifts during alpine meadow degradation - Keyu Chen; Jing Zhang; Muhammad Atif Muneer; Kai Xue; Haishan Niu; Baoming Ji (Fungal Ecology, 2023)

Bioplastics from waste biomass of marine and poultry industries - Amna Arif; Farrukh Azeem; Ijaz Rasul; Muhammad Hussnain Siddique; Muhammad Zubair; Faizan Muneer; Warda Zaheer; Habibullah Nadeem (Journal of Biosciences, 2023)

Dysregulation of butyrylcholinesterase, BCHE gene SNP rs1803274, and pro-inflammatory cytokines in occupational workers - Sosan Andleeb Khan; Mbah Ntepe Leonel Javeres; Syed Tahir Abbas Shah; Nazia Bibi; Zahid Muneer; Sabir Hussain; Eugenie Nepovimova; Kamil Kuca; Syed Muhammad Nurulain (Environmental Research, 2023)

Daily maximum rainfall estimation by best-fit probability distribution in the source region of Indus River - Muhammad Rizwan; Lubna Anjum; Qaisar Mehmood; Junaid Nawaz Chauhdary; Muhammad Yamin; Muhammad Awais; Muhammad Ansir Muneer; Muhammad Irfan (Theoretical and Applied Climatology, 2023)

Consumption of Citrus mealybug, Planococcus citri by two predators, Cryptolaemus montrouzieri Mulsant and Chrysoperla carnea (Stephen), under controlled conditions - Rehana Bibi; Munir Ahmad; Asim Gulzar; Muhammad Tariq; Muneer Ahmad (International Journal of Tropical Insect Science, 2022)

Review on integrated disease and pest management of field crops - Muneer Abbas; Muhammad Saleem; Dilbar Hussain; Muhammad Ramzan; Muhammad Jawad Saleem; Sohail Abbas; Niaz Hussain; Muhammad Irshad; Khalid Hussain; Ghulam Ghouse; Mudassar Khaliq; Zubeda Parveen (International Journal of Tropical Insect Science, 2022)

Response of dry matter partition and yield components to waterlogging and sunlight shortage in different growth stages of wheat - Min Jiang; Shouli Xuan; Muhammad Atif Muneer; Bin Sun; Chunlin Shi; Fengshan Liu; Renye Wu (Natural Hazards, 2022)

Photocatalysis: an effective tool for photodegradation of dyes—a review - Muhammad Saeed; Majid Muneer; Atta ul Haq; Nadia Akram (Environmental Science and Pollution Research, 2022)

Synthesis and characterization of ZnO decorated reduced graphene oxide (ZnO-rGO) and evaluation of its photocatalytic activity toward photodegradation of methylene blue - Asif Nisar; Muhammad Saeed; Majid Muneer; Muhammad Usman; Iltaf Khan (Environmental Science and Pollution Research, 2022)

Rainfall forecasting in upper Indus basin using various artificial intelligence techniques - Muhammad Hammad; Muhammad Shoaib; Hamza Salahudin; Muhammad Azhar Inam Baig; Mudasser Muneer Khan; Muhammad Kaleem Ullah (Stochastic Environmental Research and Risk Assessment, 2021)

Isolation and identification of low-density polyethylene degrading novel bacterial strains - Habibullah Nadeem; Khush Bakhat Alia; Faizan Muneer; Ijaz Rasul; Muhammad Hussnain Siddique; Farrukh Azeem; Muhammad Zubair (Archives of Microbiology, 2021)

Deciphering distinct biological control and growth promoting potential of multi-stress tolerant Bacillus subtilis PM32 for potato stem canker - Shehzad Mehmood; Muhammad Atif Muneer; Muhammad Tahir; Muhammad Tariq Javed; Tariq Mahmood; Muhammad Siddique Afridi; Najeeba Paree Pakar; Hina Ali Abbasi; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2021)

Land-use change affects stoichiometric patterns of soil organic carbon, nitrogen, and phosphorus in the red soil of Southeast China - Xiaojun Yan; Wenhao Yang; Muhammad Atif Muneer; Siwen Zhang; Mingkuang Wang; Liangquan Wu (Journal of Soils and Sediments, 2021)

Sustainable construction through energy management practices in developing economies: an analysis of barriers in the construction sector - Muzaffar Iqbal; Junhai Ma; Naveed Ahmad; Kramat Hussain; Muhammad Shahjahan Usmani; Muneer Ahmad (Environmental Science and Pollution Research, 2021)

Performance evaluation of participatory irrigation management as an alternative to a state‐managed irrigation system* - Sabir Hussain; Mudasser Muneer Khan; Muhammad Shoaib; Ali Raza; Syyed Adnan Raheel Shah; Tanveer Ahmed Khan; Sher Khan (Irrigation and Drainage, 2021)
The Lower Bari Doab Canal (LBDC) system is one of the large old irrigation systems in Punjab, Pakistan. To overcome problems of water distribution and management in conventional state‐managed irrigation, a participatory irrigation management (PIM) system was introduced in the LBDC command area in 2012. From the very large system of the LBDC, 20 different kinds of distributaries were selected in this study as representatives for evaluating performance of the new system. The primary data were gathered through questionnaires and by interviewing farmers, whereas the secondary data were gathered from the related offices of the Punjab Irrigation Department. The analysis of collected data illustrates that water service deliveries (WSDs) were poor even after implementation of PIM. The research shows that under administration of both systems, efficiency regarding provision of water seemed to be poor. The outcomes show that with the passage of time, recovery ( abiana ) decreased after implementation of the PIM system but the financial sustainability of PIM has improved compared to state administration. Finally, the current study recommends institutional reforms in PIM and comprehensive work on educating the farmers about their role in PIM as a mandatory component for improving efficiency of the PIM system.

Comparative Assessment of Reference Evapotranspiration Estimation Using Conventional Method and Machine Learning Algorithms in Four Climatic Regions - Ali Raza; Muhammad Shoaib; Muhammad Abrar Faiz; Faisal Baig; Mudasser Muneer Khan; Muhammad Kaleem Ullah; Muhammad Zubair (Pure and Applied Geophysics, 2020)

Microbial l-asparaginase: purification, characterization and applications - Faizan Muneer; Muhammad Hussnain Siddique; Farrukh Azeem; Ijaz Rasul; Saima Muzammil; Muhammad Zubair; Muhammad Afzal; Habibullah Nadeem (Archives of Microbiology, 2020)

Application of non-conventional soft computing approaches for estimation of reference evapotranspiration in various climatic regions - Ali Raza; Muhammad Shoaib; Afzaal Khan; Faisal Baig; Muhammad Abrar Faiz; Mudasser Muneer Khan (Theoretical and Applied Climatology, 2020)

Assessment of precipitation variability and uncertainty of stream flow in the Hindu Kush Himalayan and Karakoram River basins of Pakistan - Muhammad Abrar Faiz; Dong Liu; Qiang Fu; Dariusz Wrzesiński; Shehakk Muneer; Muhammad Imran Khan; Tianxiao Li; Song Cui (Meteorology and Atmospheric Physics, 2019)

A Comparative Study of Various Hybrid Wavelet Feedforward Neural Network Models for Runoff Forecasting - Muhammad Shoaib; Asaad Y. Shamseldin; Sher Khan; Mudasser Muneer Khan; Zahid Mahmood Khan; Tahir Sultan; Bruce W. Melville (Water Resources Management, 2018)

A wavelet based approach for combining the outputs of different rainfall–runoff models - Muhammad Shoaib; Asaad Y. Shamseldin; Sher Khan; Mudasser Muneer Khan; Zahid Mahmood Khan; Bruce W. Melville (Stochastic Environmental Research and Risk Assessment, 2018)

Photocatalytic Degradation of Pentachlorophenol Using ZnO Nanoparticles: Study of Intermediates and Toxicity - Muneer M. Ba-Abbad; Mohd S. Takriff; Muhammad Said; Abdelbaki Benamor; Mustafa S. Nasser; Abdul Wahab Mohammad (International Journal of Environmental Research, 2017)

Chaetomium endophytes: a repository of pharmacologically active metabolites - Nighat Fatima; Syed Aun Muhammad; Ibrar Khan; Muneer Ahmed Qazi; Irum Shahzadi; Amara Mumtaz; Muhammad Ali Hashmi; Abida Kalsoom Khan; Tariq Ismail (Acta Physiologiae Plantarum, 2016)

Cloning, characterization and molecular docking of a highly thermostable β-1,4-glucosidase from Thermotoga petrophila - Ikram Ul Haq; Mahmood Ali Khan; Bushra Muneer; Zahid Hussain; Sumra Afzal; Sana Majeed; Naeem Rashid; Muhammad Mohsin Javed; Ishtiaq Ahmad (Biotechnology Letters, 2012)